2020
DOI: 10.1111/cea.13598
|View full text |Cite
|
Sign up to set email alerts
|

Airway hyperresponsiveness, remodeling and inflammation in infants with wheeze

Abstract: Background:The relationship of airway hyperresponsiveness to airway remodeling and inflammation in infants with wheeze is unclear.Objective: To investigate airway hyperresponsiveness, remodeling and inflammation in infants with wheeze and troublesome breathing.Methods: Inclusion criteria were as follows: full-term, 3-23 months of age; doctor -diagnosed wheeze and persistent recurrent troublesome breathing; without obvious structural defect, suspicion of ciliary dyskinesia, cystic fibrosis, immune deficiency or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Lung eosinophilia also causes proinflammatory response during SARS-CoV2 infection and is a contributing factor to vasculitis in COVID-19 disease (64,65). We detected elevated expression of a Cytokines, growth factors, and cytotoxic granule proteins, such as CCL11, TGF-b, MBP, and ECP produced or released by activated eosinophils could lead to tissue damage and airway remodeling (67,68). CCR3 is a relatively selective chemokine receptor for eosinophils, together with its ligand eotaxins, such as CCL11, CCL24, and CCL26 induce eosinophil migration from the blood to the diseased tissue.…”
Section: Discussionmentioning
confidence: 79%
“…Lung eosinophilia also causes proinflammatory response during SARS-CoV2 infection and is a contributing factor to vasculitis in COVID-19 disease (64,65). We detected elevated expression of a Cytokines, growth factors, and cytotoxic granule proteins, such as CCL11, TGF-b, MBP, and ECP produced or released by activated eosinophils could lead to tissue damage and airway remodeling (67,68). CCR3 is a relatively selective chemokine receptor for eosinophils, together with its ligand eotaxins, such as CCL11, CCL24, and CCL26 induce eosinophil migration from the blood to the diseased tissue.…”
Section: Discussionmentioning
confidence: 79%
“…We have finally entered the much‐anticipated era of personalized medicine for asthma, and several articles evaluated biologics and the variation in individual response to these in people with asthma 25‐27 , 28‐36 , 37 , 38 Others evaluated more traditional treatments for asthma, such as corticosteroids or mechanisms that may underlie impaired airway function in asthma 39‐59 . New interventions studied in clinical trials included air cleaners, triple inhaler therapy, an oral prostaglandin D2 antagonist 60‐62 and other more preliminary data from various interventions, from cinnamon and bacterial peptides to allergen immunotherapy 63‐67 .…”
Section: Asthmamentioning
confidence: 99%
“…In 2017, the American Thoracic Society stated that the role of airway wall remodeling in asthma is insufficiently understood and needs to be further investigated [6]. Neither its origin nor its contribution to asthma is known, and the hypothesis that chronic inflammation is the only cause of airway wall remodeling has been challenged in recent years [7][8][9][10][11]. In an official workshop report of the American Thoracic Society, it was concluded that air pollution is most likely to pre-condition a child's lungs to develop asthma or COPD later 2 of 15 in life.…”
Section: Introductionmentioning
confidence: 99%
“…It has been long hypothesized that airway wall remodeling in childhood asthma is progressing over the duration of the disease and is caused by chronic inflammation. Referring to some studies on the causes of airway wall remodeling during embryogenesis and early childhood [10][11][12], this hypothesis has been challenged [13][14][15][16][17]. The earlier assumption that asthma, atopy, and bronchial hyper-reactivity are caused by genetic modifications of immune regulatory proteins was not confirmed [13,18].…”
Section: Introductionmentioning
confidence: 99%